Evolution and implementation of One Health to control the dissemination of antibiotic-resistant bacteria and resistance genes: A review - Ahmad, Nayeem; Joji, Ronni Mol; Shahid, Mohammad (Frontiers in Cellular and Infection Microbiology, 2023)
Antibiotic resistance is a serious threat to humanity and its environment. Aberrant usage of antibiotics in the human, animal, and environmental sectors, as well as the dissemination of resistant bacteria and resistance genes among these sectors and globally, are all contributing factors. In humans, antibiotics are generally used to treat infections and prevent illnesses. Antibiotic usage in food-producing animals has lately emerged as a major public health concern. These medicines are currently being utilized to prevent and treat infectious diseases and also for its growth-promoting qualities. These methods have resulted in the induction and spread of antibiotic resistant infections from animals to humans. Antibiotics can be introduced into the environment from a variety of sources, including human wastes, veterinary wastes, and livestock husbandry waste. The soil has been recognized as a reservoir of ABR genes, not only because of the presence of a wide and varied range of bacteria capable of producing natural antibiotics but also for the usage of natural manure on crop fields, which may contain ABR genes or antibiotics. Fears about the human health hazards of ABR related to environmental antibiotic residues include the possible threat of modifying the human microbiota and promoting the rise and selection of resistant bacteria, and the possible danger of generating a selection pressure on the environmental microflora resulting in environmental antibiotic resistance. Because of the connectivity of these sectors, antibiotic use, antibiotic residue persistence, and the existence of antibiotic-resistant bacteria in human-animal-environment habitats are all linked to the One Health triangle. The pillars of support including rigorous ABR surveillance among different sectors individually and in combination, and at national and international level, overcoming laboratory resource challenges, and core plan and action execution should be strictly implemented to combat and contain ABR under one health approach. Implementing One Health could help to avoid the emergence and dissemination of antibiotic resistance while also promoting a healthier One World. This review aims to emphasize antibiotic resistance and its regulatory approaches from the perspective of One Health by highlighting the interconnectedness and multi-sectoral nature of the human, animal, and environmental health or ill-health facets.